Cushing’s Syndrome due to Ectopic ACTH from Bronchial Carcinoid: A Case Report and Review - Manohara Kenchaiah; Steve Hyer (Case Reports in Endocrinology)
Despite advances in analytic and imaging techniques, the syndrome of ectopic adrenocorticotrophic hormone (ACTH) secretion from a tumour resulting in Cushing’s syndrome continues to pose difficult diagnostic and therapeutic challenges. Dynamic testing may be equivocal and radiology indeterminate. We report a patient presenting with Cushing’s syndrome associated with ectopic ACTH secretion from a bronchial carcinoid whose management presented diagnostic and therapeutic challenges.